Pelatihan Pendampingan Pengelolaan Keuangan dan Penyusunan Aplikasi Pelaporan Keuangan Masjid untuk Peningkatan Akuntabilitas Sosial - Purbaningsih, Rr Yoppy Palupi; Bachmidi, Faiz Said (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The aims of this community service activity are to provide training for mosque administrators in Istiqmal Mosque and to provide knowledge about how to prepare mosque financial reports using an Excel-based application, namely XL Akoontan. We design the mosque financial statement application that meets the criteria for Financial Accounting Standards. Therefore, the financial statement can be accurately accounted for by the people who have donated some of their wealth to the mosque. The method for implementing this service program is initial preparation, main implementation and final assessment. The results of the activity have a positive response from the members. The mosque administrators believe that the training and assistance in preparing financial reports in accordance with financial accounting standards based on the Excel program are able to improve their knowledge and ease them in preparing financial reports. The training can improve the administrator’ skills and the accuracy in financial reporting. The impact of this activity is mosque administrators can be easier and more efficient in preparing financial statements.